The relationship between the biovars and the antimicrobial resistance of Ureaplasma urealyticum in female patients with urogenital infections. Issue 1 (27th March 2017) - Zhang, Yan; Hua, Chuan; Li, Su‐li
Abstract : Background: Ureaplasma urealyticum is considered as one of the main pathogens found in women with urogenital infection. This study aimed to investigate the relationship between the biovars, serovars, and their antimicrobial resistance against antibiotics in female patients with urogenital infection. Methods: Two hundred and forty‐six cervical secretion samples (125 female outpatients as the patient group, 121 healthy female subjects as the control group) were first collected and analyzed for U. urealyticum using the Mycoplasma Identification and Antimicrobial Susceptibility Testing; then polymerase chain reaction (PCR) was carried out to identify the biovars and serovars of U. urealyticum ‐positive samples. Results: The prevalence of U. urealyticum in the patient group (57. 60%) was higher than that in the control group (24.79%, P <.01). The main biovar was biovar 1, and the main serovars were 1 (S1), 3 (S3), 6 (S6) in biovar 1. Mixed infection was observed in biovar 2. According to the results of Antimicrobial Susceptibility Testing in the patient group, biovar 1 shows more resistance to minocycline, doxycycline, and azithromycin than biovar 2 ( P <.05). Serovars S1, S3 and S6 have the highest resistant rate to ofloxacin (84.38%), roxithromycin (84.62%), and azithromycin (90.90%), respectively. Conclusions: A high prevalence of U. urealyticum was observed in female patients with urogenital infections. And the biovar 1 and the serovars 1, 3, 6 were the main types of pathogens.